Central Serous Chorioretinopathy in a Myopic Patient with Pachychoroid. Issue 1 (2017) - van Dijk, Elon H.C.; de Roon Hertoge, Kasper L.; Boon, Camiel J.F.
Introduction: To report a case of central serous chorioretinopathy (CSC) associated with a retinal pigment epithelium detachment in a myopic patient with marked pachychoroid. Patient presentation: Case report of a 37-year-old male patient with relatively high myopia (-5.00D in OD/-5.75D in OS), unilateral CSC, and bilateral retinal pigment epithelial detachments, pachychoroid, and choroidal hyperaemia. Standard ophthalmological examination and multimodal imaging, including fundus photography, fundus autofluorescence, spectral-domain and enhanced depth optical coherence tomography, and indocyanine green angiography were performed. Conclusions: Findings characteristic for the spectrum of CSC/pachychoroid pigment epitheliopathy can be observed in patients with relatively high myopia. Based on the outcome of complete ophthalmological examination, this clinical picture can be discerned from other diseases, which is important for the optimal therapeutic approach.